THE EFFECT OF REWARD AND PUNISHMENT IMPLEMENTATION ON EMPLOYEE PERFORMANCE AT THE GORONTALO FOOD AND DRUG SUPERVISORY OFFICE - Raflin Hinelo; Robiyati Podungge; Husain Ambo (SEAN Institute, 2023)
This study aims to determine the effect of reward and punishment on employee performance at the POM Office in Gorontalo both partially and simultaneously. The population in this study was all employees of the POM Center in Gorontalo. Using descriptive and verficative techniques. The population in this study was the entire ASN of the Gorontalo POM Hall as many as 51 employees. The results of the study proved that the t reward test has a significant influence on employee performance, while punishment does not have a significant effect. Based on the f test, the variables of reward and punishment together had a significant effect on the performance of employees of the POM Center in Gorontalo. For the adjusted coefficient of determination test or Adjusted R Square, which is 0.761, it means that 76.1% of the variation of all free variables (reward and punishment) can explain the dependent variables (employee performance), while the remaining 23.9% is explained by other variables that were not studied in this study.